Effect of acidified water on phenolic profile and antioxidant activity of dried blackcurrant (Ribes nigrum L.) pomace extracts - Mohamad Azman, Ezzat; Mohd Nor, Nurfarhana Diana; Charalampopoulos, Dimitris; Chatzifragkou, Afroditi (Elsevier, 2021)
This study investigated the effect of acidified water at different pH values and extraction time on the phenolic profile (anthocyanins, hydroxycinnamic acids and flavonols), antioxidant activity and colour characteristics of dried blackcurrant pomaces (DBP) extracts. Extractions were carried out using acetic acid in water (pH 1.5, 2.0, 2.5 and 3.0) for 2 and 6 h at 30 °C. Phenolics concentration in DBP extracts were influenced by the pH of acidified water (p < 0.05), while extraction pH, extraction time and their combination had significant impact on total phenolics, antioxidant activity and colour of DBP extracts (p < 0.05). Regardless of the extraction time, very low pH (1.5) was positively associated with high amounts of anthocyanins, hydroxycinnamic acids and flavonols in DPB extracts. Also, extracts obtained at pH 1.5 had the highest amount of total phenolics and antioxidant activity. Overall, acetic acid in water as extraction medium may influence greatly the phenolic profile and colour of DBP extracts, which could be utilised as alternative to synthetic food colourants.